Telaah Teoretis dan Yuridis Tukar Menukar Barang Milik Daerah dengan Swasta - rauta, umbu; Kurnia, Titon Slamet; Siswanto, Arie (Jurnal Hukum IUS QUIA IUSTUM, 2017)
This studyÂ brought upÂ the problems,Â first, the theoretical foundation of the exchange of regionalÂ ownedÂ property (BMD) between local government and private parties.Â Second, the laws and regulations governing the exchange activities of BMD.Â Third, basic considerationsÂ in relationÂ to the exchange of BMD. The type of the research was normative research. The results concluded that, first, theoretically, the government (local government) can doÂ contractualizationÂ of governmentaffairs because this has become a practice (habit) in the government. The contractualisation includes exchange agreements with non-governmental parties that involve assets(land)thatare under government control (BMD). Second, juridically, the regulational basis forÂ the exchange agreementÂ servingÂ as the basis for the right to transfer the assets (land) under government control (BMD) can be found in the legislation.Â InÂ doingÂ such actions,Â terms and conditions of legislation shall apply as the basis of the validity of the actionsÂ which includesÂ theÂ aspects of authority, substance and procedure.Â Third,Â another thing that determinesÂ the feasibility of government action in exchanging BMD (in the form of land) is the aspect of benefit (doelmatigheid).